HUSBAND'S MOTIVATIONAL RELATIONSHIP TO ANTENATAL CARE'S VISIT - Putri, Anjeli Ratih Syamlingga; Nova, Cindy Yeselti; Rahayu, Restianingsih Putri (JURNAL IBU DAN ANAK, 2020)
ABSTRACT Antenatal care is very important in reducing mortality due to childbirth. Thepurpose of this study is to determine the relationship between husband'smotivation and antenatal care visits in the Sipayung Health Center in 2017. Themethod used is analytical with a sampling technique with a random samplingtechnique. Research conducted in December 2017 in the Work Area of theSipayung Puskesmas, Rengat District, Indragiri Hulu Regency, obtained thefollowing results: the husband's motivation in the ANC visit was positive as manyas 73 people (87%) and negative as many as 11 people (13%). Of the 84people who visited the ANC, 63 people (75%) had complete ANC visits and 21(25%) were incomplete. The results of the study using bivariate analysisobtained P> 0.005 (P = 0.277). The conclusion of this study is that there is norelationship between husband's support for antenatal care visits in the SipayungHealth Center Work Area in 2017.